Short Bowel Patients Treated for Two Years with Glucagon-Like Peptide 2: Effects on Intestinal Morphology and Absorption, Renal Function, Bone and Body Composition, and Muscle Function. (3rd August 2009) - Jeppesen, P. B.; Lund, P.; Gottschalck, I. B.; Nielsen, H. B.; Holst, J. J.; Mortensen, J.; Poulsen, S.S.; Quistorff, B.; Mortensen, P. B.
Abstract : Background and aims . In a short-term study, Glucagon-like peptide 2 (GLP-2) has been shown to improve intestinal absorption in short bowel syndrome (SBS) patients. This study describes longitudinal changes in relation to GLP-2 treatment for two years. Methods . GLP-2, 400 micrograms, s.c., TID, were offered, to eleven SBS patients keeping parenteral support constant. 72-hour nutritional balance studies were performed at baseline, weeks 13, 26, 52 during two years intermitted by an 8-week washout period. In addition, mucosal morphometrics, renal function (by creatinine clearance), body composition and bone mineral density (by DEXA), biochemical markers of bone turnover (by s-CTX and osteocalcin, PTH and vitamin D), and muscle function (NMR, lungfunction, exercise test) were measured. Results . GLP-2 compliance was> 93%. Three of eleven patients did not complete the study. In the remaining 8 patients, GLP-2 significantly reduced the fecal wet weight from approximately 3.0 to approximately 2.0 kg/day. This was accompanied by a decline in the oral wet weight intake, maintaining intestinal wet weight absorption and urinary weight constant. Renal function improved. No significant changes were demonstrated in energy intake or absorption, and GLP-2 did not significantly affect mucosal morphology, body composition, bone mineral density or muscle function. Conclusions . GLP-2 treatment reduces fecal weight by approximately 1000 g/d and enables SBS patients to maintain their intestinal fluid and electrolyte absorption at lower oral intakes. This was accompanied by a 28% improvement in creatinine clearance.